Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fonc.2023.1157379
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of 2D and 3D MRI radiomics features in meningioma grade prediction: A preliminary study

Abstract: ObjectivesThe objective of this study was to compare the predictive performance of 2D and 3D radiomics features in meningioma grade based on enhanced T1 WI images.MethodsThere were 170 high grade meningioma and 170 low grade meningioma were selected randomly. The 2D and 3D features were extracted from 2D and 3D ROI of each meningioma. The Spearman correlation analysis and least absolute shrinkage and selection operator (LASSO) regression were used to select the valuable features. The 2D and 3D predictive model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…36 Although there are no studies directly comparing the performance of 2D vs 3D analysis for NME, it is supposed that observer variability is more amplified in 3D segmentation because of the need to repeatedly delineate indistinct boundaries. On the other hand, there are some reports which have compared the performance of 2D and 3D analyses in various diseases and tasks, [42][43][44][45][46][47][48][49][50] but the results have been inconsistent, and are still under debate. Among them, several studies have shown that 2D analysis had a better or equal performance than 3D analysis, suggesting that 2D segmentation can substitute 3D segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Although there are no studies directly comparing the performance of 2D vs 3D analysis for NME, it is supposed that observer variability is more amplified in 3D segmentation because of the need to repeatedly delineate indistinct boundaries. On the other hand, there are some reports which have compared the performance of 2D and 3D analyses in various diseases and tasks, [42][43][44][45][46][47][48][49][50] but the results have been inconsistent, and are still under debate. Among them, several studies have shown that 2D analysis had a better or equal performance than 3D analysis, suggesting that 2D segmentation can substitute 3D segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, several studies have shown that 2D analysis had a better or equal performance than 3D analysis, suggesting that 2D segmentation can substitute 3D segmentation. [44][45][46][47][48][49][50] The mechanism for these results is not clear, but one possible reason is that the effect of observer variability in boundary identification is amplified in 3D, 46,47,50 rendering it more error-prone. Bos et al hypothesized that interpolation to isotropic voxels, a pre-processing step for creating a VOI, may affect the performance of 3D analysis by removing relevant feature information.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the study was limited by its small sample size of 27 patients and lack of long-term follow-up. A recent radiomics study with large sample size (Duan et al, 2023) reported the differentiation of meningioma grading, using 2D and 3D features obtained only from contrast enhanced T1-weighted images. The AUC of 2D and 3D models was 0.717-0.773, which was lower than that of our methods using DTcIs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested radiomics to be promising to assist in meningioma grading, but reported performances (AUCs) widely range from 0.71 to 0.94 [11][12][13]33,[44][45][46][47][48][49][50][51][52][53]. This may be due to the majority of studies utilizing only a naïve train-test split [11][12][13]33,[44][45][46][47]49,[51][52][53] validation, with only two exiting studies reporting the average result of cross-validation (CV) folds [48,50]. However, results derived from naïve train-test splits are susceptible to selection bias and variability, and may potentially overestimate the capability of the model.…”
Section: Discussionmentioning
confidence: 99%